The determination of stability constants of para substituted n-benzylideneaniline metal complexes by a potentiometric method - (:unkn) unknown (Freund Publishing House Ltd, 2004)
In the present study, the stability constants of the complexes which were formed from N-benzylideneaniline (BDA), N-benzylidene-4-chloroaniline (BDCA), N-(4-chlorobenzylidene)aniline (CBDA), N-benzylidene-4-nitroaniline (BDNA) and N-benzylidene-4-hydroxyaniline (BDHA) with chromium (III), manganese (II), cobalt (II), nickel (II), copper (II), zinc (II) and cadmium (II) were determined potentiometrically by using Calvin-Bjerrum and Irving-Rossotti methods. The protonation constants and dissociation constants of the ligands were found at 25°C and for I=0,11 are given below: BDA logK1 - pK1 = 4,36 ; BDCA logK1 - pK1 = 3,60 ; CBDA logK1 = pK1 = 4,56 ; BDNA logK1 - pK 1 - 2,45; BDHA logK1 = pK2 = 11,05 ; logK 2 - pK1 = 5,75 The formation constants of complexes formed using Cr(III), Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) are, respectively, 3.50; 3.90; 3.21; 3.90; 2.99; 3.30 and 3.30 for BDA; 3.35; 3.05; 3.05; 2.89; 2.93; 2.88 and 2.89 for BDCA, 3.88; 3.44; 3.15; 3.30; 3.27; 3.30 and 2.98 for CBDA, 17.08; 4.56; 4.90; 5.26; 11.00; 6.52 and 4.40 for BDHA. None of these metals formed complexes with BDNA. The conditional formation constants and the pH ranges of formation of the resulting complexes were determined. The relative abundance was plotted using conditional formation constants of the complexes and the steps for the formation of the complexes were shown in graphs. The composition of metal complexes for monodentate ligands was determined as a metal/ligand ratio of 1:1. The composition of chromium and copper complexes for bidentate ligands was determined as a metal/ligand ratio of 1:2, while the ratio of other metal complexes was 1:1.
Keywords: Ligand; Metal complexes; Potentiometric titration; Stability constants